2021
DOI: 10.1017/wtc.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

Direct continuous electromyographic control of a powered prosthetic ankle for improved postural control after guided physical training: A case study

Abstract: Despite the promise of powered lower limb prostheses, existing controllers do not assist many daily activities that require continuous control of prosthetic joints according to human states and environments. The objective of this case study was to investigate the feasibility of direct, continuous electromyographic (dEMG) control of a powered ankle prosthesis, combined with physical therapist-guided training, for improved standing postural control in an individual with transtibial amputation. Specifically, EMG … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The prosthesis joint mechanics can be determined by the human feedforward neural output. This method has shown increasing success in improving various activity performance and postural control in a recent study [ 58 ]. Note that direct EMG control here is defined as a myoeletric control method for powered prostheses, which follows antagonistic muscle function around a joint for movement control.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The prosthesis joint mechanics can be determined by the human feedforward neural output. This method has shown increasing success in improving various activity performance and postural control in a recent study [ 58 ]. Note that direct EMG control here is defined as a myoeletric control method for powered prostheses, which follows antagonistic muscle function around a joint for movement control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study showed a transtibial amputee could produce anticipatory postural adjustments on an EMG-controlled prosthetic ankle to significantly improve stability after a perturbation. They also studied the ability for a transtibial amputee to control a variety of standing postural control tasks like quiet standing on firm and compliant surfaces as well as load transfer tasks [ 58 ]. The results demonstrated the ability for an amputee to significantly improve bilateral EMG activation synchronization and standing postural control with direct EMG control of a prosthesis ankle after extended, guided training with a physical therapist.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Each armband has 8 sensors in a ring that is designed to slide onto the arm to sense hand gestures. We modified and re-purposed two of these wearable armband arrays by joining them into one ring of 16 sensors to be worn over the major anterior and posterior muscles of the thigh (figure 3,4) [3,4]. A third armband array of 8 sensors is utilized to measure the calf movement and is positioned over the major muscles of the calf and lower leg (figure 5) [1].…”
Section: Sensors and Datamentioning
confidence: 99%
“…More direct approaches, in which the EMG signals are explicitly related to the control of the prosthesis have been successfully implemented and provided users with non-weight-bearing volitional control [26] [27]. More recently, an EMG controller has been used to provide volitional control of the knee extension torque provided by a powered prosthesis enabling squatting, lunging, and sit to stand transition under different loading conditions [28][29] [30] [31]. Despite these promising results, voluntary EMG controllers suffer from limitations related to the low signal-to-noise ratio and the lack of muscle specificity typical of surface EMG sensors [32].…”
mentioning
confidence: 99%